2017
DOI: 10.1016/j.proci.2016.06.161
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive simulations of viscous detonations initiated by a hot jet using a high-order hybrid WENO–CD scheme

Abstract: Abstract:In the present work a sixth-order hybrid WENO-Centered Difference (CD) scheme with an adaptive mesh refinement method is employed to investigate gaseous detonation by injecting a hot jet into a hydrogen-oxygen combustible mixture flowing at supersonic speed. Two-dimensional reactive NavierStokes (NS) equations with one-step two-species chemistry model are solved numerically. The comparison between viscous and inviscid detonation structures shows that due to the absence of both the physical viscosity i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 37 publications
1
22
0
1
Order By: Relevance
“…The highest grid resolution in case 2 of Δ min 7.8 × 10 −6 m corresponds to approximate 275 Pts∕Lhr (points per half reaction length). This has been effectively verified in the recent work [10], which shows that at least about 10 cells can be placed within the viscous scale, hence indicating that these diffusive scales can be fully resolved in the present simulations except for shock waves whose thicknesses are only several mean free path lengths.…”
Section: Convergence Analysissupporting
confidence: 80%
See 2 more Smart Citations
“…The highest grid resolution in case 2 of Δ min 7.8 × 10 −6 m corresponds to approximate 275 Pts∕Lhr (points per half reaction length). This has been effectively verified in the recent work [10], which shows that at least about 10 cells can be placed within the viscous scale, hence indicating that these diffusive scales can be fully resolved in the present simulations except for shock waves whose thicknesses are only several mean free path lengths.…”
Section: Convergence Analysissupporting
confidence: 80%
“…Overall, it is suggested that the use of the cavity can contribute to the realization of detonation stabilization especially when the incoming velocity is larger than the CJ velocity. The second promising approach for sustained detonation stabilization with hot jet initiation is the use of expanding channels, which are usually adopted in actual propulsion combustors for maximizing thrust [10]. It is found that detonation can be maintained almost in the same position after the shutdown of the hot jet due to both the Prandtl-Meyer expansion and the rapid heat release of unburned jets through the turbulent mixing and diffusion [10].…”
Section: Nomenclature Fmentioning
confidence: 99%
See 1 more Smart Citation
“…The highest grid resolution in Case 2 of min Δ =7.8×10 -6 m, which corresponds to 275 Pts/Lhr (points per half reaction length), has been effectively verified in recent works [4,10]. It is reported that the viscous scale is the smallest among the three diffusive scales (viscous shear layer, thermal heat conduction layer and mass diffusion layer).…”
Section: Convergence Analysismentioning
confidence: 60%
“…Taking into account that the actual combustors are usually expanding for thrust propulsion, recently two-dimensional detonation simulations in supersonic expanding channels have been carried out [10]. It is speculated that the detonation front can be maintained almost in the same position in the expanding channel for the given expanding angle after the shutdown of the hot jet, suggesting the formation of dynamically quasi-steady propagation of detonation.…”
Section: Introductionmentioning
confidence: 99%